(untitled) (Fiep Bulletin - online, 2011)
Introduction: The cerebral palsy is a chronic condition that causes disability since childhood until adulthood. These children being physically unable to perform some activities of the day to day, depend on caregivers. The overload of activities that these caregivers exert can lead to significant musculoskeletal changes such as low back pain which can cause disability. Objective: The research has as objective check the influence of low back pain, if present, in activities of daily living (ADLs) in caregivers of children with cerebral palsy on the clinic FAG. Methodology: This is a epidemiological study, is the type qualitative and quantitative cross-sectional with a probability sample. The sample consisted of 14 caregivers of children diagnosed with cerebral palsy of integrated clinical FAG. Initially, sociodemographic data were collected, to measure the intensity of pain was used to visual analogue scale (VAS) and after applied the Roland Morris questionnaire that assesses the level of disability in ADLs. The data were tabulated and analyzed by Microsoft Excel 2007. Results: In the analysis of sociodemographic data, 50% reported feel moderate pain. In the second part of the questionnaire, we found an average approximately 6 items marked. Theses answers, 75% change positions frequently to relieve the pain, 50% can’t get much time standing or bending and 37.5% perform ADLs slower than normal. On the total score wasn’t obtained a significant score, which is low, which proved that no influence on the ADLs of caregivers on the clinic FAG. Conclussion: We conclude that there isn’t influence of low back pain on activities of daily life of caregivers of children with cerebral palsy on clinic FAG.